In Vitro Evaluation of Dental Resin Monomers, Triethylene Glycol Dimethacrylate (TEGDMA), and 2-Hydroxyethyl Methacrylate (HEMA) in Primary Human Melanocytes: A Pilot Study - Shilpi Goenka (Oral, 2023)
Triethylene glycol dimethacrylate (TEGDMA) and 2-hydroxyethyl methacrylate (HEMA), two resin monomers often used in dental restorative materials, are leached due to insufficient polymerization and contact cells of the oral cavity. Despite reports on the cytotoxicity of these monomers on different oral cells, their effects on oral melanocytes remain unknown. This first report provides novel data on the impact of TEGDMA and HEMA monomers on melanocyte viability and functions by utilizing primary human melanocytes from lightly pigmented (HEMn-LP) foreskin as a representative model of oral melanocytes. Results show that TEGDMA induced higher cytotoxicity than HEMA and significant morphological alterations (increased dendricity) in melanocytes at the lowest concentration of 0.25 mM onwards. HEMA achieved similar effects but only at an 8-fold higher concentration (2 mM), while lower concentrations did not induce any change in cellular melanin or morphology. HEMA suppressed intracellular tyrosinase activity at 1 and 2 mM, while TEGDMA had no effect, although none of the monomers altered tyrosinase activity directly in an acellular system. TEGDMA and HEMA did not alter cellular ROS production. TEGDMA suppressed LPS-induced IL-6 cytokine secretion in cells to a greater degree than HEMA, indicating its greater capacity to dampen the immune response. Our findings demonstrate that TEGDMA and HEMA at different concentrations induce cytotoxicity to melanocytes, stimulate their dendricity and impair immune responses, indicative of altered melanocyte homeostasis. Furthermore, it is worth considering alternative monomers in light of the cytotoxicity exhibited by TEGDMA at lower millimolar concentrations compared to HEMA as well as its significant impact on melanocyte differentiation and immune function.